2014
DOI: 10.1007/s12149-014-0881-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a direct 4D reconstruction method using generalised linear least squares for estimating nonlinear micro-parametric maps

Abstract: The proposed direct parametric reconstruction algorithm is a promising approach towards the estimation of all individual microparameters of any compartment model. In addition, due to the linearised nature of the GLLS algorithm, the fitting step can be very efficiently implemented and, therefore, it does not considerably affect the overall reconstruction time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For example the generalized linear least squares (GLLS) method has been successfully applied (Angelis et al 2014, Kotasidis et al 2012. An alternative approximation would be to use f (k) EM instead of f(θ (k) ) for the weights.…”
Section: Non-linear Modelsmentioning
confidence: 99%
“…For example the generalized linear least squares (GLLS) method has been successfully applied (Angelis et al 2014, Kotasidis et al 2012. An alternative approximation would be to use f (k) EM instead of f(θ (k) ) for the weights.…”
Section: Non-linear Modelsmentioning
confidence: 99%
“…When construction of a common simple kinetic model within the imaging FOV is ensured, the aforementioned direct EM 4D framework can deliver parametric maps of improved precision and accuracy compared to post-reconstruction kinetic analysis. This has been demonstrated for both 1-tissue (Kotasidis et al 2010), irreversible 2-tissue (Angelis et al 2014 and reversible simplified reference tissue models (Gravel and Reader 2013), in perfusion, metabolism and brain imaging studies respectively. However in the presence of complex kinetics in the FOV, due to the inability to construct a common kinetic framework, model fitting errors in poorly modelled regions could potentially spatially propagate in other well modelled regions, resulting in biased parameter estimates (Kotasidis et al 2011).…”
Section: Theorymentioning
confidence: 79%
“…We are aware that recently has been shown that the brain exchange coefficients of the compartmental systems, can vary very much according to the spatial position in the organ. For this reason, the two-compartment catenary compartmental system used for describing the brain physiology is modelled, applied and reduced pixelwise [16,17,18]. Such compartmental models are known as parametric compartmental models or indirect parametric imaging.…”
Section: The Model Of the Brainmentioning
confidence: 99%